Faktor-faktor Yang Mempengaruhi Sertifikasi Halal dalam Upaya Pemenuhan Kepuasan Konsumen - Maksudi Maksudi; Bahrudin Bahrudin; Nasruddin Nasruddin (ITB AAS INDONESIA Surakarta, 2023)
The people of Pringsewu district are well-known for being religious with Islam as the religion of the majority of the population. The location of Pringsewu Regency is one of the busiest routes in Lampung Province to a number of provinces on the west coast of Sumatra, making Pringsewu Regency very potential for the development of the trade and service sector, both small, medium and large trading businesses. Pringsewu is a market for home-based bottled refill drinking water products which has the potential to become the target of domestic and foreign producers. Based on this, researchers conducted research on the factors that influence halal certification in an effort to fulfill consumer satisfaction of home-packaged refill drinking water in Pringsewu district. Considering that not all of the products available on the market have a halal certificate from the BPJPH institution. The purpose of the research conducted was to describe the effect of halal certification on home bottled drinking water businesses in an effort to fulfill consumer satisfaction in Pringsewu district, to describe the factors that influence halal certification of home bottled refill drinking water businesses in an effort to fulfill consumer satisfaction in Pringsewu District, and describes consumer perceptions of the implementation of halal certification in home-packaged refill drinking water businesses in Pringsewu District. This research is a research that uses a descriptive qualitative approach. Data collection techniques used are observation, interviews, and documentation. The informants used were 24 business actors and consumers in Pringsewu Regency, Gadingrejo District and Ambarawa District. This study found that the implementation of halal certification has not had a positive effect on home-packaged refill drinking water businesses in an effort to fulfill consumer satisfaction in Pringsewu Regency. This is due to several factors, including; there is no awareness of halal business actors, there is no socialization of halal certification from the government and BPJPH institutions, lack of knowledge and understanding of halal certification, limited capital, busyness factors, less harmonious relations between business actors, halal certification has not been considered an urgent and familiar need, and lack of consumer concern for business actors in efforts to implement halal certification.